T-cell responses to SARS-CoV-2 in healthy controls and primary immunodeficiency patients. (10th January 2022) - Awuah, Arnold; Zamani, Ava; Tahami, Fariba; Davis, Mark; Grandjean, Louis; Buckland, Matthew; Gilmour, Kimberly
Abstract: Understanding the T-cell response to SARS-CoV-2 is key in patients who lack antibody production. We demonstrate the applicability of a functional assay to measure the T-cell response in a cohort of patients with immunodeficiency. Abstract : T-cell responses to COVID are now linked to improved outcomes. This paper demonstrates a method to robustly test responses for routine diagnostic use in healthy controls and those unable to make a detectable antibody response due to underlying immune deficiency (primary or acquired). Graphical Abstract: